Performance Optimization in a Centrifugal Pump Impeller by Orthogonal Experiment and Numerical Simulation - Ling Zhou; Weidong Shi; Suqing Wu (Advances in Mechanical Engineering, 2013)
In order to improve the hydrodynamic performance of the centrifugal pump, an orthogonal experiment was carried out to optimize the impeller design parameters. This study employs the commercial computational fluid dynamics (CFD) code to solve the Navier-Stokes equations for three-dimensional steady flow and predict the pump performance. The prototype experimental test results of the original pump were acquired and compared with the data predicted from the numerical simulation, which presents a good agreement under all operating conditions. Five main impeller geometric parameters were chosen as the research factors. According to the orthogonal table, 16 impellers were designed and modeled. Then, the 16 impellers equipped with the same volute were simulated by the same numerical methods. Through the variance analysis method, the best parameter combination for higher efficiency was captured finally. Compared with the original pump, the pump efficiency and head of optimal pump have a significant improvement.